2020
DOI: 10.3390/met10030304
|View full text |Cite
|
Sign up to set email alerts
|

Wear Performance of Metal Materials Fabricated by Powder Bed Fusion: A Literature Review

Abstract: Powder Bed Fusion (PBF) is an additive manufacturing technology used to produce metal-based materials. PBF materials have a unique microstructure as a result from repeated and sharp heating/cooling cycles. Many researches have been carried out on relations between processing parameters of the PBF technology, obtained microstructures and mechanical properties. However, there are few studies on the tribological properties of PBF materials at various contact conditions. This article describes previous and recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…For this purpose, we use the substitution k z k k z k An analysis of the dispersion Equation (10) has revealed that the low frequency approximation even with included thermoelectric and evaporation capillary effects cannot provide an adequate explanation why a micro-and nanodimensional cell crystallization structure forms; we seek therefore for functions of the perturbations growth rate on the base of solutions to the dispersion Equation (9). For this purpose, we use the substitution k 1 = z 1 k, k 2 = z 2 k and ω = ω ν (z 2 − 1), z 2 = (1 + Pr(z 2 1 − 1)) 1/2 . This substitution transforms the Equation 9into an algebraic equation of the 16th degree in z 1 , which is too lengthy to be given here.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this purpose, we use the substitution k z k k z k An analysis of the dispersion Equation (10) has revealed that the low frequency approximation even with included thermoelectric and evaporation capillary effects cannot provide an adequate explanation why a micro-and nanodimensional cell crystallization structure forms; we seek therefore for functions of the perturbations growth rate on the base of solutions to the dispersion Equation (9). For this purpose, we use the substitution k 1 = z 1 k, k 2 = z 2 k and ω = ω ν (z 2 − 1), z 2 = (1 + Pr(z 2 1 − 1)) 1/2 . This substitution transforms the Equation 9into an algebraic equation of the 16th degree in z 1 , which is too lengthy to be given here.…”
Section: Resultsmentioning
confidence: 99%
“…The development of pulsed high intensity technologies with the purpose of improving strength and tribology characteristics of high-duty machine elements represents one of the challenging issues confronting the present-day material science [1]. The material fracture is known to arise in the surface and near-surface layers because long-ranging stresses in them exceed the material strength limit [2]. It is necessary therefore to generate such a structure in the material surface, which would ensure high strength properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Qin et al [31] has presented in their review that, for the Fe alloys, the main wear mechanisms are plastic deformation and oxidation. The impact of post treatments on wear and friction behavior of such parts was also shown, and presented in figure 8(a) and figure 8(b).…”
Section: Powder Bed Fusionmentioning
confidence: 99%